2013
DOI: 10.3109/09593985.2013.823582
|View full text |Cite
|
Sign up to set email alerts
|

Muscle force production with low and medium frequency burst modulated biphasic pulsed currents

Abstract: BMBPC with low frequency carrier current elicits forces approximating maximal volitional force. These findings offer new evidence with strong clinical implications when using NMES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…KFAC with burst duration of 2 ms induced higher evoked torque compared to the KFAC with burst duration of 10 ms. While Bellew et al 24,39 did not compare KFAC with different burst duration with PC, it is reasonable to expect that KFAC modulated with long phase duration or lower burst is more suitable for higher NMES-induced torque.…”
Section: Discussionmentioning
confidence: 96%
“…KFAC with burst duration of 2 ms induced higher evoked torque compared to the KFAC with burst duration of 10 ms. While Bellew et al 24,39 did not compare KFAC with different burst duration with PC, it is reasonable to expect that KFAC modulated with long phase duration or lower burst is more suitable for higher NMES-induced torque.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, 211,212 devices have been designed to deliver different configurations of the traditional Russian current with adjustable levels of carrier frequency (1000-5000 Hz), burst frequency (50-75 bursts per second), or burst duration (2-10 ms). Modulated AC therapeutic currents are normally available only on wall-powered stimulators.…”
Section: Russian Current As An Example Of Burst-modulated Ac (Bmac)mentioning
confidence: 99%
“…Although these three forms of current would be indistinguishable to a patient, some research has suggested that the ability to elicit near-maximal force without considerable discomfort can be influenced by the waveform. 211,212 Pulsed current (PC)…”
Section: Russian Current As An Example Of Burst-modulated Ac (Bmac)mentioning
confidence: 99%
“…Faradic current, Russian current, and high voltage pulsed galvanic (HVPG) currents are frequently used clinically to strengthen the healthy muscle by electric stimulation. If the frequency of the current is high enough, tetanic muscle contraction can be obtained, the same as in maximal voluntary contraction by stimulation (12). According to a study by Kots, high-intensity currents have been claimed to provide 10-30% more contractions than voluntary muscle contractions.…”
Section: Introductionmentioning
confidence: 99%